VD_FINDINFO AI 96/15 - 297/2015 vom 16. November 2015 - VD Tribunal cantonal (2015)
RENTE D'INVALIDITÉ, RENTE TEMPORAIRE, FORCE PROBANTE, RAPPORT MÉDICAL, REVENU D'INVALIDE | 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 88a al. 1 RAI